Toward defect‐free semi‐polar GaN templates on pre‐structured sapphire (Phys. Status Solidi B 5/2016). Issue 5 (6th May 2016) - Han, Yisong; Caliebe, Marian; Hage, Fredrik; Ramasse, Quentin; Pristovsek, Markus; Zhu, Tongtong; Scholz, Ferdinand; Humphreys, Colin
Abstract : There is a need for large‐size, cost‐effective and high‐quality semi‐polar GaN templates for the development of semi‐polar GaN based light emitting diodes (LEDs), which are promising to give an increased light emitting efficiency. As one of the approaches, semi‐polar templates have been successfully developed on pre‐structured sapphire (patterned) substrates. This a pproach involves an initial growth of GaN along the c‐direction followed by a coalescence between adjacent GaN stripes to form a continuous semi‐polar surface. Using transmission electron microscopy (TEM), Yisong Han et al. (pp. 834–839 ) provide a detailed microstructural characterisation of semi‐polar (11‐22) GaN layers grown by MOVPE on pre‐structured r‐plane sapphire. They focus on the study of the generation and propagation of defects as the growth progresses, and the impact of incorporating a SiN interlayer for dislocation reduction before coalescence and its microstructure on different facets. In addition, a series of Si‐doped marker layers were deposited at different stages of the growth, which provide important insight into the evolution of the GaN stripes before coalescence as a function of growth temperature.